Exploring Our Oceans: Using the Global Classroom to Develop Ocean Literacy - Fielding, Sarah; Copley, Jonathan T.; Mills, Rachel A. (Frontiers in Marine Science, 2019)
Developing the ocean literacy of individuals of all ages from all countries, cultures, and economic backgrounds is essential to inform choices for sustainable living in the future, but how we reach and represent diverse voices is a challenge. Massive Open Online Courses (MOOCs) offer a possible tool to achieve this goal, as they can potentially reach large numbers of people including those from lower and middle income regions. The number of MOOCs themed around ocean science and/or literacy is growing rapidly, and here we share experience of developing and delivering a MOOC entitled "Exploring Our Oceans", which has run ten times in the past four years with around 40,000 participants worldwide. The "Exploring Our Oceans" MOOC incorporates a blend of x-mooc and c-mooc techniques grounded in both instructivist and constructivist theories, thereby emphasising contributions from a global community of learners and encouraging individual agency in relation to ocean citizenship. The impacts of the MOOC include evidence of changed awareness and attitudes to ocean issues; increased applications and participation in undergraduate and postgraduate programmes; development of communication and outreach skills in the postgraduate community and partnership building with Nelson Mandela University, South Africa. These impacts, and vignettes of learner experiences in the course, are discussed in the context of the effectiveness of MOOCs in developing global ocean literacy.